Monetary policy implementation in a negative rate environment - Michael Boutros; Jonathan Witmer (Bank of Canada, 2017)
Monetary policy implementation could, in theory, be constrained by deeply negative rates since overnight market participants may have an incentive to invest in cash rather than lend to other participants. To understand the functioning of overnight markets in such an environment, we add the option to exchange central bank reserves for cash to the standard workhorse model of monetary policy implementation (Poole 1968). Importantly, we show that monetary policy is not constrained when just the deposit rate is below the yield on cash. However, it could be constrained when the target overnight rate is below the yield on cash. At this point, the overnight rate equals the yield on cash instead of the target rate. Modifications to the implementation framework, such as a tiered remuneration of central bank deposits contingent on cash withdrawals, can work to restore the implementation of monetary policy such that the overnight rate equals the target rate.
Keywords: E4; E40; E42; E43; G0; 330; Interest rates; Monetary policy implementation; Monetary policy framework